Liquid Friendship in Brian Lobel’s Purge - Mehmet Ünal (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
The advent of technological advancements in contemporary society has had a profound impact on our lives by greatly facilitating various aspects of human life from communication to transportation and changing not only the media people utilize in their everyday lives but also their traditions, values, and relationships. Thus, these changes have sparked debate regarding the overall positive or negative implications of these developments as the dynamic nature of all kinds of human relationships in modern times varying from everyday relationships of friendships, partnerships and sexual encounters to kinship and family has increasingly begun to be characterized by transience, fragility, ambivalence and rapid change. These characteristics are attributed to the impact of modern technological advancements, namely the proliferation of social media applications. The purpose of this study is to examine how social media applications shape relationships today with a specific focus on Brian Lobel’s Purge (2011) in light of Zygmunt Bauman’s ideas of liquid modernity. Since Brian Lobel’s Purge (2011) is a play about making the decision to end or maintain friendship through social media applications, it provides us with pertinent examples for scrutinizing the themes of transience, fragility, vulnerability and ambivalence that have become the hallmarks of the modern relationships in the age of liquid modernity.